Population structure and genetic diversity of Sinibrama macrops from Ou River and Ling River based on mtDNA D-loop region analysis, China. (17th February 2018) - Zhao, Liangjie; Chenoweth, Erica L.; Liu, Qigen
Abstract: In order to understand the influence of human activities such as habitat fragmentation on freshwater fish population evolution, we investigated and compared the genetic diversity and phylogeography of Sinibrama macrops populations in the Oujiang River and Ling River. Mitochondrial control region sequences (D-loop region) of 131 specimens from six populations were obtained and analyzed. The diversity of main stream in the Ou River was lower than that in Ling River. Changtan population showed the lowest diversity ( H  = 0.646 ± 0.077; π  = 0.00060 ± 0.00820). Pairwise FST, gene flow ( Nm ), and genetic distance ( Da ) indicated that Longquan and Changtan significantly differentiate from other populations. Nested clade phylogeographical analysis (NCPA) showed some clades and total cladogram experienced isolation by distance. In conclusion, the populations from severely fragmented Ou River have the lower diversity and more intense differentiation than that from the mainstream of Ling River, Changtan population present the lowest diversity and were isolated by the dam construction.